Dietary Benefits of Baphia nitida Stem Bark and Antimicrobial Effect on Some Pathogens: Dietary Benefits of Baphia nitida Stem Bark (Biological Sciences - PJSIR, 2020)
The need to find a broad-based nutritional and antimicrobial therapy gave impetus to this investigation. The crude extracts of Baphia nitida stem bark were used to check for antimicrobial effect on selected micro-organisms for possible nutritional and therapeutic application. The stem bark components were extracted with four solvent systems using maceration. A synthetic drug gentamycin - 80 mg/mL (2 mL) was dissolved in 20 mL of distilled water to obtained 8 mg/mL, was used as a control. The crude extract exhibited an antibacterial effect on gram-positive organisms (Staphylococcus aureus and Bacillus cereus), and gram-negative organism (Pseudomonas aeruginosa, and Escherichia coli) at 2 mg/mL. These showed competitiveness with the 8 mg/mL of the control drug. The normal hexane fraction had an effect on Staphylococcus aureus but showed no effect on other bacteria. Minimum inhibitory concentration (MIC) showed a dose-dependent decrease in the effect for the crude extract. Ethyl acetate and methanol fraction had an effect on Staphylococcus aureus, Bacillus cereus, Pseudomonas aeruginosa, and Escherichia coli at varying concentrations - 20, 10, and 5 mg/mL. the initial screening of the Baphia nitida stem bark revealed alkaloids in the methanol-methylene chloride crude extract and methanol fraction only. Other solvents showed the alkaloids, flavonoids, saponins, terpenoids, glycosides, hydrogen cyanides and steroids respectively. Therefore, the presence of the phytochemicals implicates its antimicrobial effect and the basis for its efficacy as antimicrobial therapy.